Abundance and composition of the gut contents of orbiculate cardinal fish, Sphaeramia orbicularis (Apogonidae) in Palompon, Leyte. - Canda, Danielle Clare
The study was conducted to examine the gut contents of Sphaeramia orbicularis using specimens from catches of a sled trawl survey conducted from june 2011 to May 2012 in Palompon, Leyte. One hundred seventy-one fish specimens were categorized into six different size classes maintaining an internval of 1 cm: 1-1.9 cm, 2-2.9cm, 3-39cm, 4.4.9cm, 5-5.9cm, and 6-6.9cm. The guts of the fish specimens were isolated and the contents were placed on a petri dish for identification and counting. Based on the observed percentages of chyme, the species consume a large amount of easily digested materials. The increasing number of prey items as size class increases revealed that the smaller fishes prey on a smaller organisms while the larger ones prey on the larger counterpart, and thus smaller predators are a subset of larger predators. Apogonids displayed a generalist diet, consisting mostly of demersal plankton and benthic invertebrates.